Changes in and Effects of Foreign Language Classroom Anxiety and Listening Anxiety on Chinese Undergraduate Students’ English Proficiency in the COVID-19 Context - Liu, Meihua; Yuan, Renqing (Frontiers in Psychology, 2021)
The present longitudinal survey study explored changes in and effects of foreign language classroom anxiety (FLCA) and listening anxiety (FLLA) on Chinese undergraduate students’ English proficiency over a semester in the COVID-19 context. A set of 182 matching questionnaires was collected from first-year undergraduate English as a foreign language learners at two time points of a 16-week semester. Analyses of the data revealed the following major findings: (1) the participants experienced high levels of FLCA and FLLA both at the beginning and end of the semester, neither of which changed significantly during the semester, (2) FLCA and FLLA were highly positively related to each other, (3) FLCA and FLLA significantly predicted students’ self-rated proficiency in listening and speaking English, and (4) confidence in using English, efforts and motivation to learn English and interaction with instructors and peers mediated FLCA and FLLA to exert effects on students’ self-perceived proficiency in listening and speaking English. These findings indicate that the learning environment is critical in influencing the levels of and changes in FLCA and listening anxiety and that these two types of foreign language anxiety are serious issues in the pandemic foreign language learning context.